Confiscation of Corruption Asset in The Indonesian Legal System: A Study of Criminal Law in Aceh - Syarafi, Teuku; Syahbandir, Mahdi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Confiscation of individual assets for criminal acts of corruption is important in handling corruption cases, because it is a means of recovering state losses. The confiscation of wealth aims to minimize state losses, not only must it be carried out from the start of handling the case by freezing and confiscation, but it also absolutely must be carried out in cooperation with other countries, where the proceeds of crime are located. This article examines legal policies related to asset confiscation and their alignment with criminal objectives. This research aims to analyze the rules and principles that exist in legal science. This research uses normative juridical research methods, specifically studying legal systematics to understand the fundamental aspects of criminal law. The data collection technique used was document study in the form of laws and other legal regulations, then interviews with judges in Banda Aceh. The findings reveal that the policy of confiscating assets from individuals engaged in corrupt practices can be pursued through criminal procedures, such as asset tracing, freezing, confiscation, and return. Furthermore, civil proceedings carried out by state attorneys can also facilitate the asset confiscation process. The confiscation of assets is fundamentally aligned with the purpose of punishment. It is essential to trace the assets obtained through corruption starting from the investigation stage, in order to impose restitution as an additional penalty on the perpetrators. However, obstacles arise in the actual implementation of asset confiscation. For instance, assets may have been transferred abroad by the perpetrators after being incarcerated by the court. Therefore, new legislation is required to deal with this problem.